PЕNGАRUH LEVERAGE, NILAI PASAR DAN PROFITABILITAS TERHADAP FUTURE INVESTMENT (Studi pada Perusahaan Sub Sektor Makanan dan Minuman yang terdaftar di Bursa Efek Indonesia Periode 2012-2015) - Rendi Ari Setyono; Sri Sulasmiyati (Fakultas Ilmu Administrasi Universitas Brawijaya, 2017)
This research is proposed to find out the impact of independent variable that consists of debt ratio (X1), book to market ratio (X2) and return on equity (X3) partially and simultaneously on dependent variables, investment rate (Y1) and investment opportunities (Y2). Type of research used in this research is explanatory research. The population consists about food and beverages subsector companies listed on Indonesia Stock Exchange 2012-2015 period around 10 companies that being samples based on certain criteria. Method used in this research is multiple linear regressions. The results of this study prove that: 1) on Investment Rate: a) Debt Ratio, Book to Market Ratio, and Return On Equity simultaneously have significant impact on investment rate; b) Return On Equity partially have significant impact on investment rate; c) Debt Ratio and Book to Market Ratio partially have no significant impact on investment rate. 2) on Investment Opportunities a) Debt Ratio, Book to Market Ratio, and Return On Equity simultaneously have significant impact on investment opportunities; b) Debt Ratio and Book to Market Ratio partially have significant impact on investment opportunities; c) Return On Equity partially have no significant impact on investment opportunities. Kеywords: Investment rate, Investment Opportunities, Debt Ratio, Book to Market Ratio, Return On Equity, Future Investment АBSTRАK Penelitian ini bertujuan untuk mengetahui pengaruh variabel bebas yang terdiri dari debt ratio (X1), book to market ratio (X2) dan return on equity (X3) secara simultan dan parsial tehadap variabel terikat yaitu investment rate (Y1) dan investment opportunities (Y2). Jenis penelitian ini adalah penelitian penjelasan(Explanatory Research). Populasi dalam penelitian ini adalah perusahaan makanan dan minuman yang terdaftar di Bursa Efek Indonesia Periode 2012-2015 dan didapat 10 perusahaan sampel yang terpilih berdasarkan kriteria tertentu yang disesuaikan dengan tujuan penelitian. Metode yang digunakan dalam penelitian ini adalah analisis regresi linear berganda. Hasil penelitian ini mebuktikan bahwa : 1) pada Investment Rate : a) Debt Ratio, Book to Market Ratio, dan Return On Equity secara simultan berpengaruh signifikan terhadap Investment Rate; b) Return On Equity secara parsial berpengaruh signifikan terhadap Investment Rate; c) Debt Ratio dan Book to Market Ratio secara parsial tidak berpengaruh signifikan terhadap Investment Rate. 2) pada Investment Opportunities : a) Debt Ratio, Book to Market Ratio, dan Return On Equity secara simultan berpengaruh signifikan terhadap Investment Opportunities; b) Debt Ratio dan Book to Market Ratio secara parsial berpengaruh signifikan terhadap Investment Opportunities; c) Return On Equity secara parsial tidak berpengaruh signifikan terhadap Investment Opportunities Kаtа Kunci: Investment rate, Investment Opportunities, Debt Ratio, Book to Market Ratio, Return On Equity, Future Investment